Menghidupkan legenda Sendang Kamal sebagai cerita anak berbasis multiliterasi dan kearifan loka - Bela Puji Astuti; Fida Chasanatun; Vivi Rulviana; Liya Atika Anggrasari (Prosiding Konferensi Ilmiah Dasar, 2026)
Multiliteracy refers to the ability to understand, interpret, and use various forms of information in social, cultural, and educational contexts. Strengthening multiliteracy through local folklore for elementary school children is important because students need not only reading and writing skills, but also cultural awareness and understanding of their social environment. However, low reading interest and limited use of local folktales in learning have caused regional folklore to be increasingly neglected. This study aims to describe the results of anexpedition research in developing the plot framework of the Sendang Kamal legend as a local folklore based multiliteracy learning medium in Kraton Village, Maospati District, Magetan Regency. This study used a qualitative approach with the Expedition Field Technique method through observation, in-depth interviews, documentation, and triangulation of sources and techniques to ensure data validity. The results show that the Sendang Kamal legend is related to the history of Kawambang Kulwan, Ancient Mataram, Islamic Mataram, community traditions, and local beliefs that still exist today. The study produced a plot framework based on oral history, language structure, tradition, and local wisdom. The legend contains moral values of mutual cooperation, gratitude, respect for ancestors, environmental care, and local cultural preservation.